Morpho-anatomical Characteristics as an Aid to Resolve Abies Complex in Kashmir Himalayas - Mir, Nazim Hussain; Khan, Amina (Indian Forester, 2007)
Genus Abies belongs to the family Pinaceae, large, evergreen, conical trees comprising about 40 species in the Northern Temperate Zone as well as North Africa and the Himalayas (Kashmir to Nepal). Abies is represented by four species in India. The taxonomy of Abies in Kashmir is not well understood, usually two species Abies pindrow (Lamb.) Royle and Abies spectabilis (D.Don.) Spach. Are recognized from this region. However the two species show variations with respect to needle length, sometimes specimens with mixed leaf types are seen which leads to confusion about correct identity of these species. The Gymnosperm Taxonomists perhaps for such reasons call it as 'Abies complex', because; Abies webbiana hybridizes freely with Abies pindrow forming intermediate populations in the altitudinal middle zone of their common distribution. To resolve the confusion of the complex needle anatomy of the complex has been studied. The studies were aided by the techniques of light and scanning electron microscopy, micrcotomy, micrometry and maceration technique. Characters like type of stomata their frequency, epidermal cell size, sclernchymatous hypodermis, spongy and palisade parenchyma, bundle sheath, Pericyle, nature of vascular bundles, storage tissue, resin canal shape and their position were investigated. The present studies on needle anatomy indicate that the two species are entirely different from each other. There is marked difference in the shape of epidermal cells, presence or absence of well developed hypodermis, position of resin canals in the chlorenchymatous tissue and thickness and nature of cells in the pericycle region.